Therapeutic Use of Botulinum Toxin in Neurorehabilitation. (14th September 2011) - Intiso, Domenico
Abstract : The botulinum toxins (BTX), type A and type B by blocking vesicle acetylcholine release at neuro-muscular and neuro-secretory junctions can result efficacious therapeutic agents for the treatment of numerous disorders in patients requiring neuro-rehabilitative intervention. Its use for the reduction of focal spasticity following stroke, brain injury, and cerebral palsy is provided. Although the reduction of spasticity is widely demonstrated with BTX type A injection, its impact on the improvement of dexterity and functional outcome remains controversial. The use of BTX for the rehabilitation of children with obstetrical brachial plexus palsy and in treating sialorrhea which can complicate the course of some severe neurological diseases such as amyotrophic lateral sclerosis and Parkinson's disease is also addressed. Adverse events and neutralizing antibodies formation after repeated BTX injections can occur. Since impaired neurological persons can have complex disabling feature, BTX treatment should be viewed as adjunct measure to other rehabilitative strategies that are based on the individual's residual ability and competence and targeted to achieve the best functional recovery. BTX therapy has high cost and transient effect, but its benefits outweigh these disadvantages. Future studies must clarify if this agent alone or adjunctive to other rehabilitative procedures works best on functional outcome.